DEVELOPMENT LEARNING MEDIA BASED ON MACROMEDIA FLASH ON MATRIX MATERIAL - Age Samanta Putra; Aris Thobirin (Universitas Ahmad Dahlan, 2019)
Mathematics is a compulsory subject at the secondary school level, especially on matrix material, sometimes students are still difficult to distinguish rows and columns. It is not easy to do multiplications on matrices. Learning media are expected to be a facility that supports learning. This study aims to develop learning tools based on Macromedia flash subject matter matrix class XI. In developing this learning media based on using Research and Development with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). This research was conducted at Islamic Senior High School (MA) Muallimin Yogyakarta. The research instrument used was a questionnaire. The quantitative data analysis technique calculates the score of the developed learning media's feasibility test results. The results of research on the development of interactive learning media mathematics based on Macromedia flash subject matter matrix XI based on the quality of each indicator in terms of material experts in the excellent category with an average percentage score of 86.84%, in terms of media experts in the category are very feasible with a percentage score an average of 88.33%, and student responses in the exciting category with an average percentage score of 77.37. The learning media based on Macromedia flash subject matter matrix XI class material is very feasible in the learning process.